Arsenic in Water and Food: Toxicity and Human Exposure - Pierina Visciano (Foods)
Arsenic is a human carcinogen present in drinking water and food, especially rice, rice products and seafood. It can be found in both organic and inorganic forms, the latter being the most toxic. In addition to the carcinogenic effect, exposure to inorganic arsenic can cause numerous disorders in different organs/systems of the human body, such as the skin, cardiovascular, neurological, endocrine, immune, and reproductive systems. The risk assessment associated with dietary arsenic is mainly based on the margin of exposure, i.e., the ratio between the dose at which a small but measurable adverse effect may occur and the estimated daily intake of the target substance. It is mainly influenced by arsenic concentrations and consumption data of average or 95th percentile consumers. This review focuses on the toxicity of arsenic, its sources and routes of human exposure, with particular attention to the ingestion of contaminated water and food, considering the differences between age groups and dietary habits.